Academic performance and adolescent smoking in 6 European cities - Robert, Pierre Olivier (2018)
Poor academic performance is a known risk factor for adolescent smoking, yet the association remains unclear, as the role of social ties has been rarely examined. Our study aims to investigate the role of friendship ties in this association. In a sample of 11,015 adolescents, aged 14 to17, in 50 schools within six European cities (SILNE-survey, 2013), we used multilevel models to analyse the mediating effect of the composition of friendship ties and school types on the association between academic performance and smoking. Results show smoking was more prevalent in adolescents with lower academic performance than with higher. This association was stronger in non-vocational schools than in vocational. Adolescents tended to have friendship ties with someone sharing the same smoking status and academic performance. Finally, friendship networks are patterned both on smoking and academic performance. This suggests the educational environment contributes to future socio-economic inequalities in smoking among young people.